THE INFLUENCE OF STRATEGIC LEADERSHIP AND ORGANIZATIONAL CULTURE ON STRATEGIC COMPETITIVE MEDIATED STRATEGIC PLANNING IN MANUFACTURING COMPANIES IN BEKASI DISTRICT - Zulkarnaen, Raden Ayu Atikah Permata; Setyaningrum, Retno Purwani (Universitas Muhammadiyah Tangerang, 2023)
This study aims to understand the impact of strategic leadership and organizational culture on strategic competitiveness with strategic planning being a mediating factor. This writing applies a quantitative methodology and involves 96 respondents who are a sample of workers from manufacturing companies in Bekasi Regency. Data collection for this study was carried out using the Google formular, and data processing software called SmartPLS was used. The findings of this study show that strategic leadership has a significant effect, strategic leadership has a significant effect on strategic planning, organizational culture has no significant effect on strategic competitiveness, strategic planning has no significant effect on strategic competitiveness, and strategic planning can significantly and negatively affect strategic competitive employee performance in companies manufacturing in Bekasi Regency.